Association of occupational exposures with ex vivo functional immune response in workers handling carbon nanotubes and nanofibers. Issue 3 (15th March 2020) - Schubauer-Berigan, Mary K.; Dahm, Matthew M.; Toennis, Christine A.; Sammons, Deborah L.; Eye, Tracy; Kodali, Vamsi; Zeidler-Erdely, Patti C.; Erdely, Aaron
Abstract: The objective of this study was to evaluate the association between carbon nanotube and nanofiber (CNT/F) exposure and ex vivo responses of whole blood challenged with secondary stimulants, adjusting for potential confounders, in a cross-sectional study of 102 workers. Multi-day exposure was measured by CNT/F structure count (SC) and elemental carbon (EC) air concentrations. Demographic, lifestyle and other occupational covariate data were obtained via questionnaire. Whole blood collected from each participant was incubated for 18 hours with and without two microbial stimulants (lipopolysaccharide/LPS and staphylococcal enterotoxin type B/SEB) using TruCulture technology to evaluate immune cell activity. Following incubation, supernatants were preserved and analyzed for protein concentrations. The stimulant:null response ratio for each individual protein was analyzed using multiple linear regression, followed by principal component (PC) analysis to determine whether patterns of protein response were related to CNT/F exposure. Adjusting for confounders, CNT/F metrics (most strongly, the SC-based) were significantly ( p < 0.05) inversely associated with stimulant:null ratios of several individual biomarkers: GM-CSF, IFN-γ, interleukin (IL)-2, IL-4, IL-5, IL-10, IL-17, and IL-23. CNT/F metrics were significantly inversely associated with PC1 (a weighted mean of most biomarkers, explaining 25% of the variance in the protein ratios) and PC2 (a biomarker contrast, explaining 14%). Among other occupational exposures, only solvent exposure was significant (inversely related to PC2). CNT/F exposure metrics were uniquely related to stimulant responses in challenged whole blood, illustrating reduced responsiveness to a secondary stimulus. This approach, if replicated in other exposed populations, may present a relatively sensitive method to evaluate human response to CNT/F or other occupational exposures.